Metus reverentialis jako tytuł nieważności małżeństwa w świetle wyroku Roty Rzymskiej c. Erlebach z 13 grudnia 2007 r. - Góralski, Wojciech (Ius Matrimoniale, 2015)
The author presents and comments on the judgment of the Roman Rota c. Erlebach in the matter of nullitatis matrimonii, which was passed on 13 December, 2007 in the third instance as per reverential fear (timor reverentialis). It is about the marriage concluded on 22 September, 1992 by Katarzyna and Jan. In this relationship which was concluded against the intentions of the woman one baby was born. Joint life of spouses was progressing very badly, therefore, the couple sought temporary separation several times. The definite separation of spouses took place in July, 1998 after almost six years from the conclusion of the marriage. On August 24, 1998 Katarzyna turned to the ecclesiastical court of first instance for the court to decide about the invalidity of her marriage, not indicating any other invalidity title; while she broadly presented facts regarding her case. The case was heard de facto with consideration paid to the fear on the side of the plaintiff. Having heard the plaintiff and three witnesses on her side as well as the defendant and then after taking subsequent stages of the process on 31 December, 2001 the court gave a negative judgment. After submitting by the woman of the appeal to the court of appeal and after another court hearing of Katarzyna’s mother on 14 October, 2003 the judgment was positive, while the case found its way to the Roman Rota (as the third instance), where the rota Turnus c. Erlebach (the remaining judges were A. Ciani and J. Ferreira Pena) on 13 December, 2007 issued a pro nullitate judgment.